Prophetic Theology; The Study of Criticism and Understanding of Hadith About The Existence of Allah - Mawardi Mawardi (Al-Bukhari : Jurnal Ilmu Hadis, 2021)
This article focuses on examining the existence of Allah in the hadith. Theological issue is a study that continues to develop, both internally and externally by Muslims. So far, studies on the existence of Allah SWT have only been in the study of the Qur'an and the debates of the kalam group. This study uses hadith as a basis for understanding the concept. From the study conducted, it was found that in the existence of Allah SWT is monotheism and has no beginning and no end